Reversal of idiopathic hypogonadotropic hypogonadism: a cohort study in Chinese patients - Jiang-Feng Mao; Hong-Li Xu; Jin Duan; Rong-Rong Chen; Li Li; Bin Li; Min Nie; Le Min; Le Min; Hong-Bing Zhang; Xue-Yan Wu (Asian Journal of Andrology, 2015)
Although idiopathic hypogonadotropic hypogonadism (IHH) has traditionally been viewed as a life-long disease caused by a deficiency of gonadotropin-releasing hormone neurons, a portion of patients may gradually regain normal reproductive axis function during hormonal replacement therapy. The predictive factors for potential IHH reversal are largely unknown. The aim of our study was to investigate the incidence and clinical features of IHH male patients who had reversed reproductive axis function. In this retrospective cohort study, male IHH patients were classified into a reversal group (n = 18) and a nonreversal group (n = 336). Concentration of gonadotropins and testosterone, as well as testicle sizes and sperm counts, were determined. Of 354 IHH patients, 18 (5.1%) acquired normal reproductive function during treatment. The median age for reversal was 24 years old (range 21-34 years). Compared with the nonreversal group, the reversible group had higher basal luteinizing hormone (LH) (1.0 ± 0.7 IU l -[1] vs 0.4 ± 0.4 IU l−1 , P< 0.05) and stimulated LH (28.3 ± 22.6 IU l−1 vs 1.9 ± 1.1 IU l−1 , P< 0.01) levels, as well as larger testicle size (5.1 ± 2.6 ml vs 1.5 ± 0.3 ml, P< 0.01), at the initial visit. In summary, larger testicle size and higher stimulated LH concentrations are favorite parameters for reversal. Our finding suggests that reversible patients may retain partially active reproductive axis function at initial diagnosis.